In search of a ‘new morality’ for South African education – Part VI: Values education: Realities, impediments, prospects - Schoeman, P. G. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2011)
In hierdie ondersoek sal gefokus word op die wyse waarop bepaalde diepliggende kragte die interpretasie van norme – hetsy positief of negatief – beïnvloed, asook op kondisies wat bevorderlik is vir die her-oriëntering van waarde-sisteme. In this review we will focus on the way in which profound forces – either positively or negatively – affect and shape our preferences for and interpretation of values, as well as conditions that are beneficial for the re-direction of value-systems.